The Effect of Firm Size and Profitability on Audit Delay Mediated by Audit Quality - Syaula, Ersyi; Yazid, Helmi; Taqi, Muhamad (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to determine the effect of firm size and profitability on audit delay which is mediated by audit quality, and to determine whether audit quality can mediate the relationship between firm size and profitability on audit delay. The type of research used is quantitative. The number of samples in this study were 46 companies. The data collection technique uses secondary data in the form of annual financial reports for the manufacturing sector for the 2017-2021 period which are listed on the Indonesia Stock Exchange. The analysis technique uses SEM-PLS analysis. Company Size and Profitability have an effect on Audit Delay. As well as audit quality can mediate the relationship between Firm Size and Profitability on Audit Delay.